Impact of export support: a conceptual model for export start-ups - Catanzaro, Alexis; Messeghem, Karim; Sammut, Sylvie (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
Export Start-Ups are a type of International New Ventures which has a high potential for growth and job creation. Nevertheless, they are weakened by their lack of resources and are likely to fail in foreign markets. Building on the Resources-based Theory, we ask the question of the effectiveness of Export Support Services to provide these companies with missing resources to perform in foreign markets, even though these services were originally designed for traditional exporter with internationalization by stages. We propose a conceptual model suggesting that several export services are effective and influence the knowledge, networks, and the export performance of Export Start-Ups.